Semicircular Canal Influences on the Developmental Tuning of the Translational Vestibulo-Ocular Reflex - Branoner, Francisco; Straka, Hans (Frontiers in Neurology, 2018)
Vestibulo-ocular reflexes rely on neuronal computations that transform vestibular sensory signals into spatio-temporally appropriate extraocular motor commands. The motoneuronal discharge for contractions of the superior oblique eye muscle during linear translation derives from a utricular epithelial sector that is spatially aligned with the pulling direction of this muscle. In Xenopus laevis, the alignment is gradually achieved during larval development and requires motion-related semicircular canal afferent activity. Here, we studied the origin of semicircular canal and utricular signals responsible for the establishment and maturation of the extraocular motor response vector. Experiments were conducted on semi-intact preparations of Xenopus tadpoles before and after unilateral transection of the VIIIth nerve and in preparations of animals in which semicircular canal formation was prevented on one side by the injection of hyaluronidase into the otic capsule prior to the establishment of the tubular structures. Unilateral VIIIth nerve sections revealed that the excitation underlying the contraction of the superior oblique eye muscle during horizontal linear acceleration and clockwise/counter-clockwise roll motion derives exclusively from the utricle and the posterior semicircular canal on the ipsilateral side. In contrast, the developmental constriction of the otolith response vector depends on signals from the posterior semicircular canal on the contralateral side. These latter signals suppress directionally incorrect components that derive from the utricular sector perpendicular to the superior oblique eye muscle. This directional tuning complies with a stabilization of spatially correct utricular inputs that are aligned with the extraocular motor target muscle. In addition, misaligned signals are concurrently suppressed by semicircular canal-related commissural pathways from the contralateral side and through local interneuronal inhibitory circuits within the ipsilateral vestibular nuclei.